Tu es Iuventas, czyli cesarz w zwierciadle mennictwa rzymskiego - Kluczek, Agata Aleksandra (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2015)
Tu esluventas, or the emperor as mirrored in Roman coinage (Summary) In the Roman Empire of the 3rd century crisis the title of princeps iuventus was born by: 1. caesares, 2. caesares, who were promoted to the rank of augusti, 3. augusti. It cannot be excluded, that the title of princeps iuventutis came to designate the idea of security and stabilization, the values which the reign of the dynasty seemed to secure so it was also used at the time when, in fact, there was no reigning dynasty. Besides, it was then when the coins propagating the idea of iuventas Augusti wereissued. That iuventas was supposed to give – like other virtutes – ideological sanction to the imperial power.